2000
DOI: 10.1007/s003940070019
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in body composition, physical capacities and energy expenditure in boys and girls during the onset of puberty

Abstract: The increases in physical capacities and EE during the onset of puberty indicated clear gender differences, which could be explained mainly by alterations of body composition in boys and girls, and by changes in hormonal status in boys. They also stressed the significant increase in energy requirements of children, especially boys, at an early stage of puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 21 publications
5
97
2
5
Order By: Relevance
“…11,27 According to previous research with obese adolescents, the FFM, which is the main determinant of EE, increased steeply in boys while showed the opposite trend in girls, both sexes submitted to an exercise protocol. 28 It is important to mention that, in the present investigation, after long-term multidisciplinary therapy, the obese adolescents (boys and girls) showed an increase in percentage of FFM; however, at baseline and after treatment, boys had…”
Section: Discussioncontrasting
confidence: 42%
“…11,27 According to previous research with obese adolescents, the FFM, which is the main determinant of EE, increased steeply in boys while showed the opposite trend in girls, both sexes submitted to an exercise protocol. 28 It is important to mention that, in the present investigation, after long-term multidisciplinary therapy, the obese adolescents (boys and girls) showed an increase in percentage of FFM; however, at baseline and after treatment, boys had…”
Section: Discussioncontrasting
confidence: 42%
“…Other reasons for these findings might be anthropometric characteristics predicting swimming speed such as body height [23][24][25]. Since anthropometry of an athlete changed across lifetime [26,27], certain years of life may favour elite swimming performance. Geladas et al [24] examined the relationship between anthropometry, physical capacity, and sprint swimming speed in swimmers of both sexes aged 12-14 years old.…”
Section: Change In the Age Of Peak Swimming Speedmentioning
confidence: 99%
“…Tuuri et al [30] showed that a greater fat mass in female swimmers was more strongly related to lower levels of exercise. Bitar et al [26] reported that during the onset of puberty, boys and girls gained fat-free mass, whereas fat mass gain was higher in girls than in boys. Lean body mass, which primarily reflects muscle mass, begins to increase during early puberty in both boys and girls.…”
Section: Sex Difference In the Age Of Peak Swimming Speedmentioning
confidence: 99%
“…From these studies we can conclude that the distribution and development of fat mass is different in boys and girls (1)(2)(3)(4)(5)(6). The current obesity epidemic urges us to learn more about the physiologic development of fat mass during puberty, a critical period in body composition development.…”
mentioning
confidence: 99%